ANALYZING US MAINLAND PRECIPITATION PATTERN CHANGE BASED ON A KINETICS-BASED GIS METHOD - Cui, K. (ISPRS annals of the photogrammetry, remote sensing and spatial information sciences, 2017)
Precipitation is a key type of dynamic geographic phenomena. With time changing, precipitation areas can move, merge, split or disappear. Based on existing research methods, this paper applies a kinetics-based GIS method to analyze precipitation patterns in US mainland area. Annual precipitation data of 1950 and 2010 in small spatial resolution are selected for analysis. Three major dynamic changing types are considered for analysis: divergence, rotation and deformation. Objects to analyze transitions are designed, and displacement of precipitation area is calculated. After applying kinetics-based algorithm in precipitation data, conclusions can be made that there are some significant pattern changes in some key areas of US, such as east coast, west coast and Mississippi river area. Dynamic precipitation pattern changes of divergence/convergence, rotation and deformation in different areas of US mainland are analyzed and compared.